Analysis of Parenting Values in Informal Education in The Beach Painting Film: Content Analysis Study - Rahmat Adnan Lira; Fatimah (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – This research aims to discuss the importance of exploring childcare values in informal education in the film Beach Painting, using the film Painting the Beach as the main source, and to explore data in the film that is in accordance with Islamic educational values. Design/method/approach – The type of research used is qualitative research with a narrative approach. The primary data source in this study was the Melukis Pantai (Painting the Beach) movie and secondary data sources were books, journals, and other related articles. The collected data is then analyzed using content analysis techniques using reduction, presentation and conclusion methods. Findings – The importance of informal education depicted in the Melukis Pantai movie includes 1) providing a conducive environment for children to learn, 2) providing opportunities to repeat learning, 3) parents as figures who generate positive imagination in children, 4) patience in teaching, 5) being a motivator for children, 6) not underestimating but believing in children’s abilities, and 7) parents as inspiring role models. Research Implications/Limitations – The study conducted was limited to sources and literature on the Internet. There were no interviews with the sources or respondents, the study only focused on extracting data from the movie and integrating them with other relevant sources. Originality/Value – A study with a similar theme, namely The Importance of Informal Education for Children in the Painting the Beachc movie (Analysis of Islamic Education) has not been widely conducted. Generally, it has only been theoretical, which is limited to parenting based on personal experience or sourced from characters. Therefore, this study is pure, new, and can be used as a scientific reference.